Effects of Psychosocial Rehabilitation Interventions for Schizophrenia Patients in Hospitals: Literature Review - Widoretno, Anggun Wahyu; Muji Sulistyowati (Universitas Airlangga, 2025)
Background: Schizophrenia is one of the major mental health problems in Indonesia. Pharmacotherapies alone are not sufficient, psychosocial rehabilitation interventions also should be included in the treatment plan. Handling schizophrenia using pharmacotherapy alone is not enough, psychosocial rehabilitation intervention is also needed to complement the treatment. Psychosocial rehabilitation seeks individual independence by improving psychosocial function. Many interventions can be given, but not all of them can be applied in hospitals in Indonesia. Objective: This literature review aims to identify psychosocial rehabilitation interventions in hospitals in Indonesia and how it affect for schizophrenia patients. Method: The research was conducted using Google Scholar. The keywords used was “psychosocial rehabilitation intervention, schizophrenia patient, hospital”. The searched literature is limited from 2020 -2024. Based on the search result, 10 relevant articles were obtained. Result: In all articles, psychosocial rehabilitation interventions implemented in hospitals are aimed at individuals. Interventions for families and communities have not been facilitated. The interventions found included Cognitive Behavior Theraphy (CBT), Vocational Rehabilitation, Occupational and Art Therapy (OAT), and Social Skill Training (SST). They can increase treatment adherence, reduce relapse, improve functioning, and enhance recovery. Conclusion: Psychosocial rehabilitation intervention has positive impacts for schizophrenia patient. But support from family and community will optimize the return of social function for schizophrenia sufferers.